Lesions causing freezing of gait localize to a cerebellar functional network. Issue 1 (24th January 2017) - Fasano, Alfonso; Laganiere, Simon E.; Lam, Susy; Fox, Michael D.
Abstract : Objective: Freezing of gait is a disabling symptom in Parkinson disease and related disorders, but the brain regions involved in symptom generation remain unclear. Here we analyze brain lesions causing acute onset freezing of gait to identify regions causally involved in symptom generation. Methods: Fourteen cases of lesion‐induced freezing of gait were identified from the literature, and lesions were mapped to a common brain atlas. Because lesion‐induced symptoms can come from sites connected to the lesion location, not just the lesion location itself, we also identified brain regions functionally connected to each lesion location. This technique, termed lesion network mapping, has been recently shown to identify regions involved in symptom generation across a variety of lesion‐induced disorders. Results: Lesion location was heterogeneous, and no single region could be considered necessary for symptom generation. However,  > 90% (13 of 14) of lesions were functionally connected to a focal area in the dorsal medial cerebellum. This cerebellar area overlapped previously recognized regions that are activated by locomotor tasks, termed the cerebellar locomotor region. Connectivity to this region was specific to lesions causing freezing of gait compared to lesions causing other movement disorders (hemichorea or asterixis). Interpretation: Lesions causing freezing of gait are located within a common functional network characterized by connectivity to the cerebellar locomotor region. These results based on causal brain lesions complement prior neuroimaging studies in Parkinson disease patients, advancing our understanding of the brain regions involved in freezing of gait. ANN NEUROL 2017;81:129–141